2006
DOI: 10.1007/s10654-006-9055-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papilloma virus infection in women in rural Ethiopia

Abstract: In Ethiopia cervical carcinoma is the most frequent cancer in women. HPV infection is a prerequisite for this disease. However, to date there have been no data on human papilloma virus (HPV) prevalence in Ethiopia. Outpatients attending Attat hospital in rural Ethiopia were examined for the presence of HPV DNA using the Digene HPV test. 15.9% of patients were found to be HPV positive. The proportion of HPV high risk types was 13.2% [age-standardised rates: HPV: 14.4% (95% CI: 8.5-20.2); HPV high risk: 11.6% (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
3
17
0
1
Order By: Relevance
“…Even if HPV is known to be the most common STI [26], cervical cancer is caused by HPV [27] and assumed to be imperative for medical students to have adequate knowledge about HPV infection, cervical cancer and HPV vaccine [28][29][30][31][32][33][34][35]; the overall knowledge score was not found to be adequate among the majorities of study participants. Only 43.80% were found to have adequate knowledge which is lower than the report of study findings done in different countries [22,[36][37][38] which might be because of the difference in the methodology and socio-economic conditions of the study participants and in addition most of the study participants in our study are in their pre-medicine and preclinical year of study at the university [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Even if HPV is known to be the most common STI [26], cervical cancer is caused by HPV [27] and assumed to be imperative for medical students to have adequate knowledge about HPV infection, cervical cancer and HPV vaccine [28][29][30][31][32][33][34][35]; the overall knowledge score was not found to be adequate among the majorities of study participants. Only 43.80% were found to have adequate knowledge which is lower than the report of study findings done in different countries [22,[36][37][38] which might be because of the difference in the methodology and socio-economic conditions of the study participants and in addition most of the study participants in our study are in their pre-medicine and preclinical year of study at the university [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…A prevalence of 15.9% was revealed by study done to determine the prevalence of HPV infection among women attending outpatients' clinics in Attat Rural Hospital Southern Ethiopia [18]. A retrospective molecular analysis for Human Papillomavirus on 284 formalin-fixed and paraffin-embedded cervical biopsy specimens with cervical abnormalities from the Department of pathology, Gondar College of Medical Sciences, Gondar, Ethiopia at Max-Burger Research Institute, Leipzig, Germany revealed HPV prevalence of 92.6 % in that population.…”
Section: Discussionmentioning
confidence: 99%
“…According to World Health Organization (WHO) report, the age-adjusted incidence rate of cervical cancer in Ethiopia is 35.9 per 100,000 patients with 7619 annual number of new cases and 6081 deaths every year (WHO/ICO, 2009). Moreover, facility-based studies show that cervical cancer is the leading cause of cancer in Ethiopia (Aseffa et al, 1986;Ruland et al, 2006) and other studies show that cervical cancer account for 25.8 to 32% of all female malignancies (Loutfi and Pickering, 1992;Ashine and Lemma, 1999). Despite this fact, very few women receive screening services in Ethiopia (Waktola et al, 2005).…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%